Pengaruh Teknik Distraksi Menonton Kartun Animasi terhadap Penurunan Skala Nyeri Saat Injeksi pada Anak Usia Pra Sekolah - Colin, Vellyza; Keraman, Buyung; Dwianamaydinar, Dian; Prasensi, Mahdalin (Program Studi Ilmu Keperawatan, Fakultas Ilmu Kesehatan Universitas Muhammadiyah Bengkulu, 2020)
The distraction method is a method for pain relief by diverting the patient's attention to other things so that the patient will forget about the pain he is experiencing. The purpose of this study was to determine the effect of the distraction technique of watching animated cartoons on the decrease in pain scale during injection in preschool children (3-6 years) in the Edelwis room of Dr. M. Yunus Bengkulu General Hospital. This research is a quantitative study with a pre-experimental research design using a one group pretest and posttest design. Samples of 30 respondents were taken by accidental sampling technique. Primary data collection was carried out using a pain scale questionnaire, while secondary data were obtained from related agencies that were related in this study. The results of the study, from 30 respondents there were 23 people with mild pain and 7 people with moderate pain after being treated watching animated cartoons. Based on the Wilcoxon Signed Rank Test, the Z value of -3.963 is obtained with the A symp value. Sig (Ï) = 0,000, because the value of Ï 0.05, it can be concluded that there is an influence of the distraction technique of watching animated cartoons to reduce the pain scale in pre-school children when injecting in the Edelweis room of Dr. Yunus Bengkulu General Hospital. It is expected that health workers and the community can be more focused on care for children when the child is hospitalized in undergoing hospitalization.Â Keywords: Distraction Technique, Watching Animated Cartoons, Pain Scale